Deed - Smith, Rod, 1962- (Kuhl House poets., 2007)
A deed is a governmental conveyance, a power asserted by the written, for, as William Carlos Williams wrote to Robert Creeley: "the government can never be more than the government of the words." The question of ownership, of the words with which we define ourselves and each other, and of whose and what claims are legitimate is much at issue in Rod Smith's Deed, a lyric, ambitious, rebellious work thoroughly grounded in the New American tradition of poets such as John Ashbery, Allen Ginsberg, and Charles Olson.